PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PROBLEM POSING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA MUHAMMADIYAH 1 PEKANBARU - Elvina Br Tambunan; Rini '; Jimmi Copriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrac: The research aims to increase the students achievement on the subject colloid in class XI IPA SMA Muhammadiyah 1 Pekanbaru. This research is a kind of experiment research with randomized control group pretest-posttest design. The samples of this research were the students of class XI IPA 2 as the experimental class and students of class XI IPA 4 as the control class. Experimental class is a class that is applied cooperative learning model with Problem Posing type while the control class was not applied. Data analysis technique used the t-test. The result of research showed tarithmetic>ttable that was 4,82 > 1,67 that mean the application cooperative learning model with Problem Posing type can to increase the students achievement on the subject colloid in class XI IPA SMA Muhammadiyah 1 Pekanbaru with N-gain is 0,82 that mean category of enhancement's students achievement high category.Key Word : Problem Posing, Achievement, Colloid